Awaken - Cabot, Meg (2013)
"Seventeen-year-old Pierce Oliviera knew by accepting the love of John Hayden, she'd be forced to live forever in the Underworld. But now her happiness and safety are threatened because the Furies have discovered that John has broken one of their strictest rules, and the only way to fix the balance is for someone to die"--
"An Abandon novel"--Jacket.
Keywords: Supernatural -- Fiction; Persephone (Greek deity) -- Fiction; Hades (Greek deity) -- Fiction; Erinyes (Greek mythology) -- Fiction; Love -- Fiction; Death -- Fiction; Mythology, Greek -- Fiction; Family life -- Florida -- Fiction; JUVENILE FICTION / Social Issues / Dating & Sex; JUVENILE FICTION / Love & Romance; JUVENILE FICTION / Legends, Myths, Fables / Arthurian; Florida -- Fiction